Modifikasi Permukaan Kayu Pinus Menggunakan Metode Finishing Tradisional Jepang – Yakisugi pada Beberapa Level Pengarangan (PERENNIAL, 2023)
The yakisugi method is traditionally carried out by tying three boards together to form an elongated triangle and then burning until black charcoal is created on the wood surface evenly. Based on the efficiency of application, the yakisugi method is more efficient and simple than other heat treatment methods. In Indonesia, this method has not been widely developed both on a research and industrial scale. Therefore, this study aims to evaluate the quality of yakisugi finishing on pine wood with parameters such as the length of the burning process (20 seconds and 30 seconds on a 70 cm2 area). The results showed that the pine wood burning process produced higher dimensional stability than pine without burning treatment with ASE values reaching about 56% at a burning time of 30''. Meanwhile, in the mechanical properties test, yakisugi methode provide lower values of  MOE and MOR than the control sampel. Changing in wood properties to become more brittle after the combustion process is the main reason for this phenomenon. The combustion characteristics show that the duration of combustion does not give a different color change in the test sample after the charcoal cleaning process. However, the thickness of the charcoal produced at 30" showed a higher value of 4.5 mm.
Keywords: Key words: pine wood, yakisugi, wood charring, heat treatment modification